2004
DOI: 10.1111/j.1463-5224.2004.04052.x
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of matrix metalloproteinase activity in equine tear fluid during corneal healing in 10 horses with ulcerative keratitis

Abstract: Ulcerative keratitis in horses is associated with initially high levels of tear film proteolytic activity that decrease as the ulcers heal. The success of medical and surgical treatment of the corneal ulcers is reflected by the enzyme activity in tears. In horses successful treatment does lead to a rapid reduction in tear film proteolytic activity that corresponded with the improvement in the clinical signs of corneal ulceration. Measurement of MMP activity in the tear film might represent a way to monitor the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 33 publications
1
50
0
6
Order By: Relevance
“…Matrix metalloproteinases are thought to play a pathological role in the degradation of extracellular matrix components such as basement membrane collagen; same as those found in corneal basement membrane and stroma [18]. They have also been shown to be upregulated in ulcerative fungal keratitis in rabbit as well as in the tear film of horses with ulcerative keratitis and hence are thought to play a probable role in the pathogenesis of fungal keratitis [52,134]. However, the exact role of fungal proteases in mycotic keratitis needs further investigations.…”
Section: Toxigenicitymentioning
confidence: 96%
“…Matrix metalloproteinases are thought to play a pathological role in the degradation of extracellular matrix components such as basement membrane collagen; same as those found in corneal basement membrane and stroma [18]. They have also been shown to be upregulated in ulcerative fungal keratitis in rabbit as well as in the tear film of horses with ulcerative keratitis and hence are thought to play a probable role in the pathogenesis of fungal keratitis [52,134]. However, the exact role of fungal proteases in mycotic keratitis needs further investigations.…”
Section: Toxigenicitymentioning
confidence: 96%
“…Acera et al [30] found significantly elevated pro-MMP-9 levels in blepharitis, allergic eye disease, dry eye and conjunctivochalasis. An increased expression of MMP-2 has been demonstrated in chronic inflammatory processes, which can result in the perforation of the cornea in both humans [31] and horses [32,33]. Similarly, the expression of active MMP-2 and -9 correlated with the severity of ulceration or burn trauma [34,35].…”
Section: Discussionmentioning
confidence: 94%
“…A MMP-9 encontra-se presente após danos corneais, induzindo à destruição de estruturas adesivas da membrana basal das células epiteliais, retardando, por conseguinte, a reepitelização corneal (OLLIVIER et al, 2003;BOVELAND et al, 2010). Em córneas ulceradas, a atividade das proteinases encontra-se significativamente aumentada no filme lacrimal pré-corneal (STRUBBE et al, 2000;OLLIVIER et al, 2004).…”
Section: Desenvolvimentounclassified
“…Em alguns casos, a associação do soro com EDTA pode ser necessária. A acetilcisteína, entretanto, é desencorajada por alguns autores por romper a estabilidade do filme lacrimal (OLLIVIER et al, 2003;OLLIVIER et al, 2004) Corticosteroides são totalmente contraindicados e não devem ser empregados, tampouco na redução cicatricial de uma úlcera micótica, pois o fungo pode permanecer latente no estroma. Esses medicamentos têm sido implicados no aumento da multiplicação fúngica ou na predisposição à ceratomicose (BROOKS & MATTHEWS, 2007).…”
Section: Tratamento Médicounclassified